Islamophobia_Discrimination Against Muslims in America in Attempt to Maintain Global Hegemony - Sayyidah ‘Nisa (Universitas Muhammadiyah Yogyakarta, 2022)
2 and has spread since 9/11 when a terrorist attack brought down the Twin Towers of the World Trade Center (WTC) in New York. In its history, America is the inheritor of the